Analisis Faktor Motivasi Yang Mempengaruhi Kinerja Aparatur Kecamatan Martapura Kota Di Kabupaten Banjar - Witanti, Sri (Fakultas Ekonomi Universitas Gresik, 2023)
This study was conducted to determine whether motivational factors affect the performance of the apparatus in Martapura District, Banjar Regency, in addition to knowing which factors are the most dominant, as well as how much variance the contribution of motivational factors to the performance of the sub-district apparatus. Data obtained from the distribution of questionnaires and interview results and supported by documentaries. Because the population is relatively small, the technique used is total sampling. Data analysis using the help of the SPSS program through multiple regression analysis techniques. The results showed that simultaneously and partially the motivation variables were shown to have a significant effect on the performance of the apparatus, and the variance of contributions showed 90.8% on the performance of the apparatus, while 9.2% was determined by other factors outside this study. While the most dominant variable is the need for awards with a value of 2,207.